2002
DOI: 10.1021/ar010151m
|View full text |Cite
|
Sign up to set email alerts
|

Multiwall Carbon Nanotubes:  Synthesis and Application

Abstract: Chemical vapor deposition (CVD) is the most promising synthesis route for economically producing large quantities of carbon nanotubes. We have developed a low-cost CVD process for the continuous production of aligned multiwall carbon nanotubes (MWNTs). Here we report the effects of reactor temperature, reaction time, and carbon partial pressure on the yield, purity, and size of the MWNTs produced. A simple method for purifying and healing structural defects in the nanotubes is described. The dispersion of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
250
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 668 publications
(258 citation statements)
references
References 29 publications
(42 reference statements)
3
250
0
5
Order By: Relevance
“…Other studies have also shown that amorphous carbon appears at temperatures above a window of 800 to 825 °C. 26 Also, the relationship between growth temperature and the density of CNTs on carbon fibre surfaces has been previously investigated. 27 This previous work suggests that a very low number of CNTs form at 700 °C due to the low solubility of carbon in the iron catalyst at temperatures lower than the carbon-iron eutectic temperature of 723 °C.…”
Section: Processing and Morphology Of Cnf/cntsmentioning
confidence: 99%
“…Other studies have also shown that amorphous carbon appears at temperatures above a window of 800 to 825 °C. 26 Also, the relationship between growth temperature and the density of CNTs on carbon fibre surfaces has been previously investigated. 27 This previous work suggests that a very low number of CNTs form at 700 °C due to the low solubility of carbon in the iron catalyst at temperatures lower than the carbon-iron eutectic temperature of 723 °C.…”
Section: Processing and Morphology Of Cnf/cntsmentioning
confidence: 99%
“…16 Os nanotubos foram utilizados como recebidos e apresentam diâmetro médio de 73,5 nm e comprimento médio de 7,4 mm, determinados por MEV (o comprimento foi obtido de 16 nanotubos isolados e não curvos em regiões de baixa concentração da amostra, enquanto que o diâmetro foi acessado de 55 nanotubos). A imagem MEV apresentada na Figura 1S, material suplementar, é típica da amostra utilizada e mostra a presença de nanopartículas, além de nanotubos.…”
Section: Produção Dos Nanocompósitos Tpu/mwcntunclassified
“…In this case the growth rate is nearly constant for approximately three minutes and then suddenly stops. This catalytic sudden-death has been reported elsewhere (26)(27)(28), but the mechanism still remains as an open question in this field.…”
Section: Gas Phase Thermal Decompositionmentioning
confidence: 56%